A Mucin-Like Protein Is Essential for Oviposition in Nilaparvata lugens - Lou, Yi-Han; Shen, Yan; Li, Dan-Ting; Huang, Hai-jian; Lu, Jia-Bao; Zhang, Chuan-Xi (Frontiers in Physiology, 2019)
Mucins play a variety of roles; for example, in vertebrates, mucins lubricate epithelial surfaces and protect tissue from physical and biological damage; however, knowledge of insect mucins is limited. Here, we identified an eggshell-related mucin-like protein, NlESMuc, in the brown planthopper (BPH), Nilaparvata lugens. NlESMuc was specifically expressed in the follicular cells from the egg chambers of the ovarioles. RNA interference (RNAi) was used to perform functional analysis of NlESMuc. Adult female BPH with NlESMuc knockdown had significantly reduced fecundity, including more difficult oviposition, lower egg production, and eggs that could not hatch. Scanning electron microscopy showed that, in NlESMuc knocked-down BPH, the ultrastructure of the eggshells of fully developed oocytes was loose, and the cross-section showed many small droplets of about 0.1-μm diameter. Based on the results, it is concluded that NlESMuc is an eggshell-related protein and essential for normal oviposition. Our findings help to provide new targets for pesticide design and RNAi-based BPH control and will also provide new insights into insect eggshells and insect mucins.